Courseware for primary school Science syllabus in plants life process / Muhammad Hareez Ibrahim - Ibrahim, Muhammad Hareez (2015)
Courseware is one of a learning medium which can be use in helping the learners to improve their skills and knowledge. This courseware will help student in understanding about plants in their plants life process by using pedagogical agent for student within range of age from 10-12 years old. A problem was found in traditional learning such as traditional learning consume more time to learn and conducting experiment. The developed project can help shorten the learning time for student and teaching time for instructor. The objective of this courseware is to develop a courseware that can help student in learning about plants life process using humanoid agent. The development tools used to develop this courseware is Adobe Flash Professional CS6, Audacity and Adobe Photoshop CS6 and will be representing in Windows platform. The courseware was developed based on the ‘Kurikulum Standard Sekolah Rendah (KSSR)’ Science syllabus and the methodology used is ADDIE Model which included five phases which are analysis, design, development, implementation and evaluation. The result after using this courseware show some improvement in student test percentage from 43% to 63%. New features will be add in the future works such as 3D plant and more interactive.